Pengaruh Latihan Plyometric terhadap Kecepatan Tendangan Sabit pada Peserta Ekstrakurikuler Pencak Silat di SMP Negeri 1 Pancalang Kabupaten Kuningan - Dani Nurdiansyah; Didi Muhtarom; Erdin Waluyo (LPPM Politeknik Pratama, 2024)
The purpose of this study was to determine the effect of training using Plyometric on sickle kick speed in pencak silat extracurricular participants at Smp Negeri 1 Pancalang, Kuningan Regency. This research uses a quantitative approach. The research method used is experimental research. The population used was extracurricular pencak silat participants at SMP Negeri 1 Pancalang, totaling 30 students. The sample used in this study was 15 students. VIII grade students as many as 4 students and VII grade as many as 11 students. The sampling technique in this study used purposive sampling technique which is included in non-probality sampling. This study uses an experimental method using the